1911 Colo. Sess. Laws 408 - (:unkn) unknown (General Publisher, 1911)
Required the record registration of every retail sale, rental, exchange of firearms, pistols, or revolvers. Violators guilty of a misdemeanor, punishable by a fine of not less than twenty-five, nor more than one hundred dollars, or imprisonment not exceeding one year, or both.
--
Keywords: REGISTRATION